2015
DOI: 10.3141/2488-04
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Time-of-Day Transitions for Arterial Traffic Signals

Abstract: Time-of-day operation (i.e., the implementation of different signal settings at different times of the day) is commonly used in traffic signal operation to accommodate time-dependent traffic patterns. In the current practice of signal retiming, traffic engineers rely largely on engineering judgments to determine the proper time-of-day transitions; this approach may lead to inefficient operations. For such a deficiency to be reduced, in this research an easy-to-use approach was proposed to fine-tune time-of-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The TS-Diagram is a convenient and popular tool for traffic engineers to evaluate performance of signal coordination, and to fine-tune signal settings if necessary. The procedure to construct TS-Diagram is based on Zheng et al (2015), and the result is shown in Fig. 15 for the selected corridor with the 5 intersections for time period 8 AM-9 AM.…”
Section: Mapementioning
confidence: 99%
“…The TS-Diagram is a convenient and popular tool for traffic engineers to evaluate performance of signal coordination, and to fine-tune signal settings if necessary. The procedure to construct TS-Diagram is based on Zheng et al (2015), and the result is shown in Fig. 15 for the selected corridor with the 5 intersections for time period 8 AM-9 AM.…”
Section: Mapementioning
confidence: 99%
“…Several studies have addressed the retiming of traffic signals during the last few decades; we give a detailed review of those studies in the following section. A novel trend, called Automated Traffic Signal Performance Measures advocates recording and collecting traffic signal data at a higher resolution (logs recorded with 10 Hz frequency) for improving the monitoring of traffic signals and understanding their operations (12)(13)(14). Such high-resolution (HR) signal data show great promise in modifying the way we optimize traffic signals.…”
mentioning
confidence: 99%